Definitions dynamic viscosity of nominal fixed frictional contact at the vibration loading - Костогриз, С.Г.; Шалапко, Ю.І.; Слащук, В.О.; Слащук, О.О. (Problems of Tribology, 2016)
The exact definition of dynamic viscosity of nominal fixed frictional contact can be obtained only from laboratory studies. Research conducted at the stand for testing materials under dynamic contact load. Installing enables to explore ma-terials and coating for durability and wear resistance nominal-fixed contact with small amplitude relative movements of the scheme: ball-plane, the plane-plane and profile connections. Were obtained the waveforms, what show loop of hysteresis: movement of the sample and tangential efforts. Note the "abnormally" large initial amplitude of oscillation, which is several times higher than the contact forces in extreme points of the hysteresis loop. Much of the accumulated elastic strain energy is transformed into one of the higher modes of oscillation, which is the basis of the lower mounting counter-sample. The value of dynamic viscosity of contact is determined by the relative magnitude of the signal. It does not affect the outcome of the study. It can be concluded, that dynamic viscosity of contact in terms of vibration load stationary frictional contact steel parts far exceeds the viscosity of melts iron and steel, but is significantly lower than the known tabulated values of dynamic viscosity solid iron under normal conditions. This value the viscosity of the order exceeds ultra-thin layer of liquid lubrication limit for modes of boundary friction.